PENERAPAN PEMBELAJARAN POLA PBMP (PEMBERDAYAAN BERPIKIR MELALUI PERTANYAAN) UNTUK MENINGKATKAN KETERAMPILAN METAKOGNISI DALAM PEMBELAJARAN BIOLOGI PADA SISWA KELAS X MIA-2 SMA NEGERI 8 MALANG - Ninik Kristiani (Universitas Sebelas Maret, 2014)
This research is a class act. This study aims to determine the application of learning patterns PBMP (Empowerment Through Thinking Questions) to increase awareness of metacognition in learning Biology MIA in class X - 2 at SMAN 8 Malang . This research was conducted during two cycles , each cycle includes stages : 1) initial Reflection / pre-action, 2) action planning, 3) Implementation and observation , 4) Reflection. The number of students in the class XMIA - 2 as many as 34 students . After analyzing the data , metacognition skills in the first cycle was 56.8 while the second cycle of 70.5. This metacognition skills measured using metacognition rubric (adapted from Corebima, 2011). This column is used to determine the metacognition skills by analyzing the answers to the written test in narrative form of KD 3.7 and 3.8. The conclusion of this research study PBMP patterns can improve the skills of metacognition in learning biology at XMIA - 2 grade students of SMAN 8 Malang . The author gives advice to other researchers to integrate pattern into PBMP teaching models on Curriculum 2013. Key words : learning patterns PBMP, metacognition skills , high school biology subjects